Oral health knowledge and practices of antenatal mothers in Hospital Universiti Sains Malaysia - Muhammad Azim Syahmi Kamaruddin; Norsamsu Arni Samsudin (Faculty of Dentistry, Universitas Gadjah Mada, 2019)
Mothers play a very significant role in influencing the oral health status of the family. Many studies have highlighted the importance of good oral health during pregnancy. This study aimed to assess knowledge, self-perceived oral health status, and practices of antenatal mothers in Hospital Universiti Sains Malaysia, Kelantan, Malaysia. A total of 76 antenatal mothers visiting Obstetrics & Gynaecology specialist clinic at Hospital USM were involved in this cross-sectional survey study. The questionnaires contained items related to oral health knowledge, self-perceived dental problems, barriers to seeking dental care, oral hygiene habits, perceptions of oral health, and access to dental care. Majority (98.7%) agreed that their oral health was important as part of general health. About 58% of them had answered correctly regarding oral health knowledge. Most respondents had self-perceptions of having dental problems during pregnancy, including cavitated teeth (34.4%) and sensitive teeth (20.5%). Regarding practice, only 35.3% visited a dentist in the last six months. Time constraints (52.4%) and safety concerns regarding dental treatment (26.2%) were the main barriers to seek dental care. Many (90%) brushed their teeth at least twice daily with adult fluoridated toothpaste, while some used mouthwash daily (36.8%) and flossed their teeth (11.8%). Antenatal mothers had an average level of knowledge regarding oral health, experienced dental problems during pregnancy and lacked awareness of a regular dental visit. Hence, there is a need for more vigorous oral health promotion, which also include antenatal care providers, to improve oral health awareness among antenatal mothers.